Concepções e práticas do ensino de leitura em inglês no ensino médio - O'Connell, Daniel Mateus [UNESP] (2015)
National and international indicators (ENEM, PISA) point out serious problems in the teaching and learning of reading in our native language in this country. In the case of foreign languages, the situation is even worse, especially regarding high schools where teaching is expected to prepare the student for entry into a labor market in which English is becoming increasingly important. Considering the unsatisfactory results regarding the teaching of English reading, as well as the scarcity of research on reading instruction geared specifically for this level of basic education, a research was proposed in order to identify the theoretical and methodological conceptions of two High School English teachers about the different models of reading and how they are present in their practice. Our theoretical framework included authors who dealt with the process of initial and continual training of foreign language teachers, as well as reading models and approaches to the teaching of foreign languages and pedagogical practice. In this qualitative, ethnographic research, the instruments used were: a) classroom observation of two public-school teachers in two cities in São Paulo, working in this level of education; b) semi-structured interviews with the teachers to identify their concepts on reading instruction and to clarify doubts about some aspects of the observed teaching practice; c) field notes; d) analysis of teaching materials used. The data obtained in the interview were categorized as follows: a) initial and continued teacher training; b) approach and didactic materials; c) reading conceptions and d) reading practices. The main results of the interview and classroom observation indicated: a) dissatisfaction with the initial training of both, regarding the relationship between theory and practice; b) lack of specific opportunities for the continual training of English language teachers; c) influence of experiences in the trajectory of the...